The ?“Goodbye? Petrovka”? Plan: ?Moral ?Economy? of ?File ?Sharing? in ?Post?Soviet? Ukraine - Haigh, Maria (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2014)
Ukraine, the second most populous of the former Soviet republics, had been named as one of the ten “priority countries” with “unacceptable piracy rates.” Kiev’s open-air Petrovka Market has become a symbol for the blatant distribution of pirated books, films, music, and software. As living standards and disposable incomes have… L’Ukraine, la deuxième ex-république soviétique la plus peuplée, est reconnue comme l’un des dix « pays prioritaires » pour son « taux de piratage inacceptable ». Le marché en plein air de Petrovka à Kiev est devenu un symbole flagrant de la distribution de livres, films, musique et logiciels piratés. Comme le niveau de vie et le revenu disponible ont augmenté de façon spectaculaire…